Subungual osteochondroma of great toe: a unique presentation - Sai, Reddy L.; Mandal, Tufan; Kumar, Manoj (International Journal of Research in Orthopaedics, 2024)
Osteochondroma is routinely encountered in daily practice. It is often considered as developmental aberration rather than a true neoplasm. It arises due to enchondral growth from cortex adjacent to metaphysis. Osteochondroma is usually encountered in femur, fibula and humerus in more than fifty percent of cases. It is rarely encountered in phalanges of toes and fingers. In very few cases this tumor affects small bones, localizing to the distal phalanx and producing deformity of the overlying nail. These cases are termed subungual osteochondromas and are altogether with subungual exostosis the most common bony lesions affecting the nail unit. Osteochondromas of the nail unit are often asymptomatic and present as firm nodules, nail deformity, tender on palpation. Many of these cases are associated with history of trauma. A 11-year-old male presented to us with an abnormal outgrowth of right great toe. The out growth was preceded by a history of trauma 10 days before the presentation. The swelling surface consisted of granulation tissue and bleeding spots were found on the surface. The swelling is fixed to the underlying bone and seems to have caused the destruction of nail plate. Biopsy revealed osteochondroma of the great toe with no malignant transformation and atypical cells.